EOQ (Economic Order Quantity) ANALYSIS OF RICE AVAILABILITY IN PUBLIC BULOG COMPANY IN LHOKSEUMAWE CITY - Salsabila Akmali Akmali (Institute of Computer Science (IOCS), 2020)
The research aims to find out that the implementation of rice orders at the Lhokseumawe Bulog Public Company has used the EOQ method well and the performance of rice availability management at the Lhokseumawe Bulog Public Company. The location of this research was chosen deliberately with the consideration that the area is one of the densely populated areas so it requires a large stock of rice, but the area is still classified as an area with low rice production compared to other areas in Aceh. The method of determining the sample in this study uses purposive sampling with a research sample of 11 respondents who are employees of the Public Company Bulog Lhokseumawe in each field. The data of this study were obtained from secondary data and primary data which are related to the EOQ (Economic Order Quantity) analysis. Data analysis was carried out by quantitative descriptive method where data analysis used the EOQ (Economic Order Quantity) method. The results showed that the implementation of ordering rice at the Bulog Lhokseumawe Public Company had not been carried out properly and the management performance of the Lhokseumawe Bulog Public Company was not running well.